Diacylglycerol lipase regulates lifespan and oxidative stress response by inversely modulating TOR signaling in Drosophila and C. elegans. - Lin, Y.H.; Chen, Y.C.; Kao, T.Y.; Lin, Y.C.; Hsu, T.E.; Wu, Y.C.; Ja, W.W.; Brummel, T.J.; Kapahi, P.; Yuh, C.H.; Yu, L.K.; Lin, Z.H.; et al. (Aging Cell, 2014)
Target of rapamycin (TOR) signaling is a nutrient-sensing pathway controlling metabolism and lifespan. Although TOR signaling can be activated by a metabolite of diacylglycerol (DAG), phosphatidic acid (PA), the precise genetic mechanism through which DAG metabolism influences lifespan remains unknown. DAG is metabolized to either PA via the action of DAG kinase or 2-arachidonoyl-sn-glycerol by diacylglycerol lipase (DAGL). Here, we report that in Drosophila and Caenorhabditis elegans, overexpression of diacylglycerol lipase (DAGL/inaE/dagl-1) or knockdown of diacylglycerol kinase (DGK/rdgA/dgk-5) extends lifespan and enhances response to oxidative stress. Phosphorylated S6 kinase (p-S6K) levels are reduced following these manipulations, implying the involvement of TOR signaling. Conversely, DAGL/inaE/dagl-1 mutants exhibit shortened lifespan, reduced tolerance to oxidative stress, and elevated levels of p-S6K. Additional results from genetic interaction studies are consistent with the hypothesis that DAG metabolism interacts with TOR and S6K signaling to affect longevity and oxidative stress resistance. These findings highlight conserved metabolic and genetic pathways that regulate aging.